儒家為什麼反對超人類主義？: Why does Confucianism Oppose Transhumanism ? - YANG, Qianqian (International Journal of Chinese & Comparative Philosophy of Medicine, 2021)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. The concept of human enhancement is a key to understanding transhumanism. According to Confucian ethics, the supervision of human enhancement technology is vital because we are facing the reasonable expectation of achieving “the unity of heaven and man.” (The idea of harmony between man and nature is not exclusive to Confucianism; it can be found in other schools of thought in the pre-Qin dynasty period, especially the philosophy of Taoism. However, the idea is uniquely expressed and developed in Confucianism.) Furthermore, human enhancement makes people unable to “settle in their place.” Therefore, Confucianism cannot accept it.